Theoretical discussion on internationalisation of the firm in business studies - Vijay Narayanan (International Entrepreneurship Review, 2016)
Internationalisation and the involved processes such as globalisation and Europeanisation have many different dimensions, horizons, perspectives and levels. As internationalisation is an ongoing process, it is not possible to provide an universal definition for it (Wach, 2014, Narayanan, 2015) and what is more internationalisation can be researched into at three levels – macro (economy), meso (industry) and micro (firm). In the current generation of increasing internationalisation with advancements in communication, firms around the world are trying to expand into foreign markets. Expanding into international markets may provide benefits like new and profitable businesses, facilities to develop new ideas, make innovations in manufacturing and in new technologies (Knight, 2000; Hollensen, 2007). The main objective of the paper is to discuss the concept of the internationalisation of the firm in business studies. The article is based on in-depth literature review and its critics.